Terrorism Mitigation Strategies in the Horn of Africa Region - Priscah Munyiva Mulinge, Martin Ouma (Journal of Diplomacy and International Studies, 2021)
The study sought to explore terrorism as an emerging security concern in Horn of Africa region, and the region’s mitigation strategies. The study was based on the relative deprivation theory. The study utilized secondary data, by reviewing existing studies that relate to the topic of the study. The study found that terrorism manifests itself in Horn of Africa region in three forms. First, is local terrorism. Second, is local terrorism with regional association. Third is terrorism acted by international actors with regional and local associations. Different strategies have been applied by both governments and non–governmental associations tryingnto address the effect of terrorism on society. These include establishment of commissions, humanitarian mediation, joint effort with governments and government organizations and counterterrorism policies among others. The study concludes that the strategies have, however, not been effective, as enabling drivers to terrorism and poor governance structures give rise to terrorism which in turn affect national security through terrorist activities.